Territorial development of Guanacaste, Costa Rica, from the perspective of territorial agri-food production systems - Porras Acevedo, Stephanie (2018)
The objective of this article is to identify the territorial factors that promote or hinder the establishment of a territorial agri-food production system (STPA), from a territorial development perspective, in the canton of Carrillo in the province of Guanacaste, Costa Rica. Due to the dynamism that the province has experienced in recent years and the displacement of agricultural activity since the 1990s due to tertiary activity, the aim is to investigate those factors that promote growth, considering the conditions that current projects, such as the creation of the PIMA Regional Market in Carrillo, the expansion of the cargo terminal at Daniel Oduber Quirós Airport in Liberia, and the construction of the dry canal from La Cruz to Puerto Limón, can offer. As a result of the analysis, the components of a territorial agri-food production system for the province are proposed, considering the characteristics of the companies and the synergy that these actors must have with the institutions. The article concludes that STPAs promote a high degree of association and linkages between companies, government, and available resources. It also includes the environment as a variable to be considered in the processes. Overall, STPAs can be considered an alternative for promoting food security and sovereignty in the regions by supplying the market with local products.